Association between antenatal care visits and under-five mortality: An Analysis of the Pakistan demographic and health surveys - Rashed Nawaz; Shaoqing Gong; Yaxin Zhao; Neelum Khalid; Zhongliang Zhou; Muhammad Waseem (PLoS ONE, 2025)
Background Pakistan has the third highest under-five mortality rate globally and minimal progress in reducing it, obstructing its achievement of Sustainable Development Goals (SDGs) 3.2 targets. Despite a decline, Pakistan remains one of the top ten contributors to worldwide under-five mortality. Proper antenatal care (ANC) is vital for improving maternal and child health outcomes. This study aims to assess the association between ANC visits and under-five mortality. Moreover, this study also measures the association between the timing of ANC visits and under-five mortality. Methods A difference-in-difference (DID) study design with propensity score matching (PSM) was employed to investigate the contributing impact of ANC on the estimation of under-five mortality rates. Statistics from two datasets, 2012 and 2018, of Pakistan demographic and health surveys (PDHS) have been utilized for analyses. This research sample consists of 15698 women aged 15–49 who attended ANC visits at varying times before childbirth. Results This study has reported 730 cases of under-five mortality. 98% involved Women who had less than eight or more ANC visits, whereas 2% of under-five mortality cases occurred among those women who had eight or more ANC visits. Overall, our results showed that women who had 1–3 ANC visits reduced the likelihood of under-five mortality in Pakistan by 36% (CI=0.459–0.909, P-value 0.012), the women who had 4–7 ANC visits decreased the likelihood of under-five mortality by 45% (CI=0.364–0.843, P-value 0.006). Moreover, the females with eight or more ANC visits also reduced the likelihood of under-five mortality by 98% (CI=0.512–1.896, P-value 0.966). Conclusions Policies and programs focusing more on ANC visits should be implemented to reduce under-five mortality rates significantly. By emphasizing timely and frequent ANC visits, these insights support the development of targeted interventions that can significantly improve child survival rates and support the achievement of SDG targets. Moreover, based on our DID analysis, the implementation of the free maternal and child healthcare (MCH) policy in Pakistan has led to a significant increase in ANC utilization and a consistent reduction in the under-five mortality rates.